Decellularized tissue engineered hyaline cartilage graft for articular cartilage repair - Nie, Xiaolei; Chuah, Yon Jin; Zhu, Wenzhen; He, Pengfei; Peck, Yvonne; Wang, Dong-An (Biomaterials, 2020)
Articular cartilage repair has been a long-standing challenge in orthopaedic medicine due to the limited self-regenerative capability of cartilage tissue. Currently, cartilage lesions are often treated by microfracture or autologous chondrocyte implantation (ACI). However, these treatments are frequently reported to result in a mixture of the desired hyaline cartilage and mechanically inferior fibrocartilage. In this study, by combining the advantages of cartilage tissue engineering and decellularization technology, we developed a decellularized allogeneic hyaline cartilage graft, named dLhCG, which achieved superior efficacy in articular cartilage repair and surpassed living autologous chondrocyte-based cartilaginous engraftment and ACI. By the 6-month time point after implantation in porcine knee joints, the fine morphology, composition, phenotype, microstructure and mechanical properties of the regenerated hyaline-like cartilaginous neo-tissue have been demonstrated via histology, biochemical assays, DNA microarrays and mechanical tests. The articular cartilaginous engraftment with allogeneic dLhCG was indicated to be well consistent, compatible and integrated with the native cartilage of the host. The successful repair of articular chondral defects in large animal models suggests the readiness of allogeneic dLhCG for clinical trials.